2022
DOI: 10.1007/s00531-022-02200-6
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering Carboniferous–Permian continental paleoenvironments in eastern equatorial Pangea: facies and sequence stratigraphy investigations in the Autun Basin (France)

Abstract: This work is part of the PhD thesis of MM and was funded by the BRGM and the Région Bretagne. The authors thank C. Hue, M. Buisson, T. Boucher, M. Boussaid and A. Saloume for participating in the core logging and Rock-Eval analyses, D. Chabard (director of the Natural History Museum of Autun) for access to the cores, Prof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…The structural and palaeoenvironmental settings of C-P basins of the northern Massif Central (France, Fig. 1b) have been re-evaluated and documented in a number of recent studies (Beccaletto et al 2015;Ducassou et al 2019;Garel et al 2017;Mercuzot et al 2021aMercuzot et al , 2021bMercuzot et al , 2022Luccisano et al, 2022).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…The structural and palaeoenvironmental settings of C-P basins of the northern Massif Central (France, Fig. 1b) have been re-evaluated and documented in a number of recent studies (Beccaletto et al 2015;Ducassou et al 2019;Garel et al 2017;Mercuzot et al 2021aMercuzot et al , 2021bMercuzot et al , 2022Luccisano et al, 2022).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Paris, Aquitanian and SE basins), where they can reach several hundred of km 2 (Beccaletto et al 2015). Recently, Mercuzot et al (2021aMercuzot et al ( , 2022 suggested that the original extent of the present-day basins was significantly larger, raising the idea that (i) these basins could have been connected together at the time of their infilling, and (ii) that the subsurface basins represent the lateral extension of the exposed basinal strata (Beccaletto et al 2015). Consequently, the present disparate exposures may represent preserved depocenters of the larger basins.…”
Section: The French Massif Central Carboniferous To Permian Basinsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent sedimentological study has postulated that this locality represents a marginal lacustrine environment (Mercuzot 2020; Mercuzot et al . 2022).…”
Section: Geological Settingmentioning
confidence: 99%